Determination of microbiological quality of the hot springs of Yura during of months of September to December, 2017 - Marghori Vargas Mahaney (2019)
In Arequipa is the Yura Spa, a very busy place by local and foreing tourists, here we found wells with thermo-medicinal waters to treat different illnesses. The thermal waters are waters from underground layers of Earth with very high temperaturas and high concentration of minerals, therefore, the man makes use of these waters for consumption and therapeutic applications. However, these properties of wáter can be affected by contact air, soil and up to the man, being detrimental to the health of the same. in the present investigation, it was determined the microbiological quality of the hot springs of Yura, the Most Probable Number (MPN) was used to determine the presence and recount of Total Coliforms, Thermotolerant Coliforms and Enterococcus faecalis, selective media were used to the presence of Salmonella and Pseudomonas aeruginosa, the first four microbiological parameters were compared with the Supreme Decree N° 002-2008-MINAM. Physicochemical parameters were analysed in situ using a multiparameter HANNA HI9811-5 and turbidimeter TU430. The results showed that of the total of the samples analyzed found 1.67% with presence of Thermotolerant Coliforms, 3.33% of E. faecalis that exceeded the established parameters by the Supreme Decree, found ausence of Salmonella and Pseudomonas aeruginosa was found in a 26% from the studiedsamples. It concluded that thermal waters from Yura are suitable to use according to the Supreme Decree N° 002-2008-MINAM to recreational waters respect to Total Coliforms, Thermotolerant Coliforms, E. faecalis and Salmonella.